When consumers become good soldiers: understanding the motivations and inhibitors of helping behavior among consumers - Martins, Renata Monteiro (2022)
This dissertation examines consumer citizenship behavior (CCB) in consumer-to-consumer (C2C) interactions. Specifically, I investigate the conditions in which helping behaviors among consumers are more likely to occur, as well as their motivations. Companies have been addressing their efforts to develop strategies to increase consumer engagement, focusing on building long-term relationships. There is also increasing research on C2C interactions, investigating consumers as cocreators of value. Yet, little attention has been given to helping behaviors among consumers. I explore this phenomenon in three papers. Given the lack of studies exploring C2C helping as a focal construct and that no previous research has tested the integration of its antecedents, the first paper innovates by proposing a conceptual framework of C2C helping through a meta-analytic review. The findings provide future research possibilities to explore this concept, also demonstrating its main antecedents and potential moderators. In the second paper, I propose identifying the motivations behind citizenship behaviors in consumer networks using netnography and semi-structured interviews. Consumer networks are important for marketing practitioners since they increase consumer loyalty and long-term relationships. Social network theorists also highlight the importance of understanding the role of networks’ structure in shaping individuals’ behavior to build strong and cohesive networks. However, no research investigates the different motivations for helping behaviors according to the networks’ structure. My contributions rely on pointing out such motivations and potential inhibitors based on different tie strength settings. Finally, in the third paper, I investigate the role of social comparison in C2C helping. The way consumers see themselves compared to others – especially in the virtual environment, where social comparison is intensified – has not been analyzed as a driver of helping among consumers. Through three experimental studies and a survey, I show that consumers who feel better-off than others help more than those who feel worse-off due to self-enhancement. This mediator also has not been explored in previous studies. These three papers present relevant implications to service and relationship marketing literature, combining elements from multidisciplinary approaches, especially social psychology theories.